Integrated Strategy For A Healthy Golden Generation In Rejosari Village, Ngampel District, Kendal District - Elvina Nabila Setyaningtyas; Nahidh Ubyyu Asji Ahmad; Ahmad Michael Zamzami; Nurul Kimalatul Khoiriyah; Kuni Wafiqotuz Zahroh; Rachmandanu Tri Prasojo; Septiyani Dwi Anggraeni; Hamdan Husein Batubara (PROSIDING SEMINAR NASIONAL PENDIDIKAN, BAHASA, SASTRA, SENI, DAN BUDAYA, 2024)
Stunting is a significant public health problem, which impacts the growth and development of children, and can hinder their future. This research aims to assess the effectiveness of the stunting prevention program implemented in Rejosari Village, Ngampel District, Kendal Regency. This program includes a variety of actions, including education about nutrition, distribution of additional food, and raising awareness about the importance of balanced nutrition and hygiene. The research method used is descriptive qualitative, with data collection techniques through observation, interviews and documentation. The research results show that this program is effective in reducing stunting rates in the village, increasing community understanding about nutrition, improving children's nutritional status, and the importance of personal hygiene. It is hoped that these results can be used as a reference for other regions in efforts to prevent stunting and to improve overall public health.